Titratable acidity of beverages influences salivary pH recovery - TENUTA,Livia Maria Andaló (2015)
A low pH and a high titratable acidity of juices and cola-based beverages are relevant factors that contribute to dental erosion, but the relative importance of these properties to maintain salivary pH at demineralizing levels for long periods of time after drinking is unknown. In this crossover study conductedin vivo, orange juice, a cola-based soft drink, and a 10% sucrose solution (negative control) were tested. These drinks differ in terms of their pH (3.5 ± 0.04, 2.5 ± 0.05, and 5.9 ± 0.1, respectively) and titratable acidity (3.17 ± 0.06, 0.57 ± 0.04 and < 0.005 mmols OH- to reach pH 5.5, respectively). Eight volunteers with a normal salivary flow rate and buffering capacity kept 15 mL of each beverage in their mouth for 10 s, expectorated it, and their saliva was collected after 15, 30, 45, 60, 90, and 120 s. The salivary pH, determined using a mini pH electrode, returned to the baseline value at 30 s after expectoration of the cola-based soft drink, but only at 90 s after expectoration of the orange juice. The salivary pH increased to greater than 5.5 at 15 s after expectoration of the cola drink and at 30 s after expectoration of the orange juice. These findings suggest that the titratable acidity of a beverage influences salivary pH values after drinking acidic beverages more than the beverage pH.